Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

just use z instead of 0 + z * t in section 11. #389

Open
Pomax opened this issue Dec 10, 2023 · 1 comment
Open

just use z instead of 0 + z * t in section 11. #389

Pomax opened this issue Dec 10, 2023 · 1 comment

Comments

@Pomax
Copy link
Owner

Pomax commented Dec 10, 2023

It's more confusing than useful.

@Haiderahandali
Copy link

Haiderahandali commented Dec 11, 2023

Here is my logic behind it
We have our range of t as follows:
0 <= t<= 1
We want to split it (let's say at t =1/3) such that, As t varies from 0 to 1, our
Our range varies from 0 to to 1/3
(the original way I did it is multiplying the range above by value z, so our range becomes: 0 <= t*z <= z, which is exactly what we wanted, but I knew this would not work for the second case, because if wanted to start from z and not 0, we have to shift our entire range by z so it becomes
z <= t+z <= 1+z
But this is wrong because at t = 1 our range is 1+z, so we have to multiply t by some constant ( say c) such that z + ct=1
So at t = 1, c =1-z
So as t varies from 0 to 1
z+t(1-z) varies from z to 1)

Below is a more systematic way of arriving at the same result.

So we have to replace t by the simplest possible equation, the linear equation!
a + bt, for some constants a and b.
(actually it's affine but everyone calls it linear)
We want to start from t=0 our range starts at 0, so we have
a + bt = 0 (at t =0)
a + 0*b=0
Then a = 0
We want at t = 1, our range becomes 1/3
So we have
a + bt = 1/3
Sub a = 0, t =1
Then our equation becomes instead of t, we have 1/3t.

So now, in order to split the original range from 0 to 1 we replace t by t*z and we get our range to vary from 0 to z.

In the exact same manner if we split at value z, and want to transform our range from 0 to 1 into a new range from z to 1
We have:
a +bt.
At t = 0 we want to start at value z,
a + bt = z
Sub t = 0
a +b 0= z, then a = z
At t = 1, we want our range to be 1:
a + bt = 1
Sub a=z, t=1
z = 1
b = 1
b = 1-z
Then to map our range from (originally from 0 to 1) into z to 1 we replace t by
z + (1-z)t

That is why we replace t by t*z in our first range
And t by z+t(1-z)
In the second range
I hope it made sense.

Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment
Labels
None yet
Projects
None yet
Development

No branches or pull requests

2 participants